1991
DOI: 10.1007/bf02387817
|View full text |Cite
|
Sign up to set email alerts
|

Induction time approach to surface induced crystallization in polyethylene/poly (ɛ-caprolactone) melt

Abstract: The surface induced crystallization of poly(e-caprolactone) (PCL) on an ultra-high modulus polyethylene (PE) fibre was investigated using a new approach based on the induction time t i. This approach allows estimation of the free energy difference function A~ as it appears in the theory of heterogeneous nucleation. The classical approach based on the rate of heterogeneous nucleation / is not applicable to transcrystallization because the nucleation density at the fibre surface cannot be measured. A relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…The nucleation ability of a polymer‐polymer interface will be determined by the ratio of Δσ to Δσ 0 , representing the interfacial free energy difference of the nucleated polymer. Δσ 0 /Δσ >1 would indicate favorable surface nucleation conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleation ability of a polymer‐polymer interface will be determined by the ratio of Δσ to Δσ 0 , representing the interfacial free energy difference of the nucleated polymer. Δσ 0 /Δσ >1 would indicate favorable surface nucleation conditions …”
Section: Resultsmentioning
confidence: 99%
“…Δσ 0 /Δσ >1 would indicate favorable surface nucleation conditions. [38] In order to investigate the surface nucleation phenomenon in the PLA/EBA-GMA blend, a number of crystallization study experiments were conducted in this study. PLA, being a slow crystallizing polymer having a relatively long induction time of crystallization and a low spherulitic growth rate, does not experience noticeable crystallization during cooling from the melt at a 10 °C min -1 cooling rate, unless a nucleating agent or interface having sufficient nucleating activity is present.…”
Section: Observation Of Interface Nucleation Phenomenon By Dscmentioning
confidence: 99%
“…For extremely active substrates, m D 0, and for inert substrates, m D 1. Nucleation ef ciency of the carbon bers has been also analyzed by the Muchova-Lednicky method [41,42], where the nucleation parameter Q has been calculated as an intercept of the extrapolation of the function ln.t i 1T / vs f .1=T 1T /, applying the induction time approach [9]. The values of the parameter Q decreased by increasing the carbon bre content (from ¡4.96 for iPP to ¡21.32 for C /iPP model composites).…”
Section: Nucleation Effect Of the Bersmentioning
confidence: 99%
“…In fact, many authors have reported that higher mechanical properties and interface strength resulted from the transcrystalline structure, although the concept has provoked many controversies [5 -7]. An approach for the energetic quanti cation of the transcrystallization process was reported by Ishida and Bussi [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…For these reasons, few of the papers dealing with transciystals reported AO values. Recently, the induction time approach has been proposed as a new method to study transcrystallization (34,35). When an isothermal heterogeneous crystal growth takes place, a threshold period exists when the formation and remelting of the precursors of nuclei takes place.…”
Section: Adhesion Of Thermoplastics To Substratesmentioning
confidence: 99%